Person-organization commitment: bonds of internal consumer in the context of non-profit organizations - Juaneda-Ayensa, Emma; Clavel San Emeterio, Mónica; González-Menorca, Carlos (Frontiers in Psychology, 2026)
From an Organizational Behavior perspective, it is important to recognize the links generated between individuals and the organization that encourage a desire for permanence. After more than a half century of research, Organizational Commitment remains one of the open questions in the Psychology of Organizations. It is considered an essential factor for explaining individual behavior in the organization such as satisfaction, turnover intention, or loyalty. In this paper, we analyze different contributions regarding the nature of the bond between the individual and the organization. Taking into account the peculiarities of Non-profit Organizations, we present different interpretation for later validation, comparing results from the Confirmatory Factor Analysis of the four models obtained using exploratory factor analysis, both conducted on a sample of 235 members of Non-profit Organizations.
Keywords: non-profit organizations; affective commitment; continuity commitment; normative commitment; confirmatory factor analysis